Interrogative Construction in Aceh Language - Maria Ulfa; Mulyadi Mulyadi (JURNAL ARBITRER, 2020)
The article deals with the interrogative construction in Aceh language. This study used a qualitative approach. The study aims to find out; (1) kinds of interrogative words in Aceh language (2) interrogative construction in Aceh language by using X Bar Theory. The data in this study are Acehnese sentences that contain Interrogative words. The data sources in this study are (1) Acehnese dictionaries, (2) Acehnese Book, and (3) Acehnese speakers. The data collection process by an interview with the Acehnese speaker in Langsa and data analysis used X Bar Theory. The results of the study show that;1) there are eight kinds of interrogative words in Aceh language especially in East Aceh dialect in Langsa such as: a) Pue. peue, b) Soe, c) Hoe, d) pat, dipat, e) pajan, f) pakon, g) padum, h) pane, i) pakiban. There are three categories of interrogative construction;(a) Open Interrogative, (b) Close Interrogative, (c) Rhetoric Interrogative. The Structure of the sentence in Aceh language constructs by using of the specifier, complement, and Verb. Specifiers put by NP and Complement put by Auxiliary, PP, or NP and Adverb can be preposition by PP or NP.